Phytochemical Analysis and Antioxidant Activities of Gymnema sylvestre R. Br. Leaf Extracts - Behera, Suraj Kumar (Free Radicals and Antioxidants)
Objective: The present study aims to determine the antioxidant properties and phytochemical screening of Gymnema sylvestre plant. Materials and Methods: The qualitative and quantitative analyses were carried out for the methanol extract using standard procedures. The antioxidant activities were carried out by DPPH free radical, OH- radical, H2O2 radical, O2 - radical and phosphomolybdenum reduction assay. Results: The leaves of G. sylvestre methanol extract showed good radical scavenging as well as reducing power activities. The total phenolic and flavonoid content were 19.87 ± 0.32 mg/g and 2.65 ± 0.12 mg/g respectively. Conclusion: The methanol extract of leaves of G. sylvestre possesses significant antioxidant activities.
Keywords: Antioxidant; Total phenolic; Flavonoid; Gymnema sylvestre